New aspects in the approach to building anti-corruption policy in Kazakhstan - Toleubekova Б.Х.; Khvedelidze Т.Б.; Kalkayeva Н.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The anti-corruption policy of Kazakhstan occupies an important place in the structure of the national policy of the state to combat crime. The purpose of the study is to identify the advantages of the new state anticorruption policy, expressed in the short-term concept of counteraction, compared to the long-term strategy of struggle, which Kazakhstan previously adhered to. The main methods of research are a comparative description of approaches and results of Kazakhstan’s anti-corruption policy, and the construction of a working hypothesis of the prospects for further improvement of the new model of anti-corruption policy in the transition from strategy to the concept. Achieved Results: The conceptualization of the country’s anti-corruption policy compared with the strategy is more effective due to its flexibility, allowing a timely response to any changes contributing to the growth of corruption.